DONOR SELECTION: GENERAL ASPECTS - Pereira, Simone Cunha Maradei; Souza, Aline Miranda; Bouzas, Luis Fernando; Oliveira, Danielli Cristina Muniz de (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION